Immunological Analysis of Aerobic Bioreactor Bovine Theileriosis Vaccine - Gholamreza Habibi (Iranian Journal of Parasitology, 2014)
Background: In this study, the pilot production of aerobic bioreactor tropical theileriosis vaccine was optimized with the aim of immunological assays for further mass production.